Losac and Lopap Recombinant Proteins from Lonomia obliqua Bristles Positively Modulate the Myoblast Proliferation Process - Alvarez, Angela María; Alvarez-Flores, Miryam Paola; DeOcesano-Pereira, Carlos; Goldfeder, Mauricio Barbugiani; Chudzinski-Tavassi, Ana Marisa; Moreira, Vanessa; Teixeira, Catarina (Frontiers in Molecular Biosciences, 2022)
The pursuit of better therapies for disorders creating deficiencies in skeletal muscle regeneration is in progress, and several biotoxins are used in skeletal muscle research. Since recombinant proteins derived from Lonomia obliqua bristles, recombinant Lonomia obliqua Stuart-factor activator (rLosac) and recombinant Lonomia obliqua prothrombin activator protease (rLopap) act as cytoprotective agents and promote cell survival, we hypothesize that both rLosac and rLopap favour the skeletal muscle regeneration process. In the present work, we investigate the ability of these recombinant proteins rLosac and rLopap to modulate the production of key mediators of the myogenic process. The expression of myogenic regulatory factors (MRFs), cell proliferation, the production of prostaglandin E2 (PGE2) and the protein expression of cyclooxygenases COX-1 and COX-2 were evaluated in C2C12 mouse myoblasts pre-treated with rLosac and rLopap. We found an increased proliferation of myoblasts, stimulated by both recombinant proteins. Moreover, these proteins modulated PGE2 release and MRFs activities. We also found an increased expression of the EP4 receptor in the proliferative phase of C2C12 cells, suggesting the involvement of this receptor in the effects of PGE2 in these cells. Moreover, the recombinant proteins inhibited the release of IL-6 and PGE2, which is induced by an inflammatory stimulus by IL-1β. This work reveals rLopap and rLosac as promising proteins to modulate processes involving tissue regeneration as occurs during skeletal muscle injury.